Assessing prognosis of chronic lymphocytic leukemia using biomarkers and genetics. (1st September 2020) - Moia, Riccardo; Patriarca, Andrea; Mahmoud, Abdurraouf Mokhtar; Ferri, Valentina; Favini, Chiara; Rasi, Silvia; Deambrogi, Clara; Gaidano, Gianluca
ABSTRACT: Introduction: Chronic lymphocytic leukemia (CLL) is a clinically and genetically heterogenous disease. Genomic studies have deciphered the pathogenesis of CLL and has allowed the identification of prognostic and predictive biomarkers. During the last decade, the treatment options for CLL have expanded significantly, posing the need for the identification of molecular predictors for treatment tailoring. Areas covered: This review focuses on biomarkers revealed by investigations of CLL molecular genetics and immunogenetics, and that may help optimizing therapy for individual patients. In addition, the manuscript discusses minimal residual disease (MRD) assessment and its potential application as a prognostic biomarker and as a new tool to guide treatment duration. Expert opinion: The availability of a variety of treatment options, including chemoimmunotherapy (CIT) and biological drugs that inhibit the B cell receptor (BCR) and the B cell lymphoma 2 (BCL2) antiapoptotic protein, has significantly improved survival of CLL patients. In this therapeutic landscape, the identification of different CLL risk groups based on the presence of specific molecular lesions and/or immunogenetic features has allowed treatment tailoring in terms of choosing the most appropriate drug. The combination of genetic and immunogenetic biomarkers together with MRD assessment may allow one step forward in the precision medicine approach to CLL.